Relasi Komunitas Muslim Dan Hindu Di Bengkulu: Studi Interaksi Sosial Masyarakat Desa Suro Bali - Adinda Tessa Naumi; Bakti Komalasari; Arsil Arsil; Eka Apriyani (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Suro Bali is one of the villages in Bengkulu province where the people are involved in ethnic and religious interaction, especially, Hindu and Muslim communities. Furthermore, an intense interaction for decades certainly has an impact on Muslim society. This paper is intended to determine the impact of socio-religious interactions on the Muslim community in Suro Bali. The phenomenological perspective or interpretive perspective is a big umbrella from the perspective of symbolic interaction which is the guideline in this study with a focus on the interaction of the dominant communities in Suro Bali, who are Hinduism and Islam.The result show that the effect of social-religious interaction on Muslim communities in Suro Bali can be seen from several aspects. Among other things: tolerance practices, religious activities, cultural identity, intercultural life.